Abnormal sensation during total body irradiation: a prospective observational study. (11th July 2022) - Mizumoto, Masashi; Oshiro, Yoshiko; Miyamoto, Toshio; Sumiya, Taisuke; Shimizu, Shosei; Iizumi, Takashi; Saito, Takashi; Makishima, Hirokazu; Numajiri, Haruko; Nakai, Kei; Okumura, Toshiyuki; Sakae, Takeji; et al.
Abstract: Light flash and odor during radiotherapy are well-known phenomena. Two prospective observational studies have indicated that 55% of patients observed a light flash during irradiation of the retina and 27% of patients sensed an odor during radiotherapy for the nasal cavity. A prospective observational study was performed in all patients at our hospital who received total body irradiation (TBI) between January 2019 to October 2021. Light flash and odor during TBI were examined using the same method as that used in previous studies. A total of 32 patients received TBI during the study period. The patients had a median age of 41 (18–60) years, and included 20 males and 12 females. A survey checklist showed that 14 patients (44%) sensed light and 14 patients (44%) sensed odor during TBI, . The color of the light during irradiation was yellow in six cases, white in four cases, and blue in four cases. The intensity of the light was 2–5 (median 3, 1 is very weak, 5 is very strong) and the time over which the light flash was felt was 4–60 s (median 10 s). Two patients each sensed smells of plastic, ozone and bleach, and others sensed one smell each. The intensity of the odor was 1–4 (median 3, 1 is very weak, 5 is very strong) and the time over which the odor was sensed was 1–25 s (median 3 s). We conclude that light flashes and odors are each sensed by 44% of patients during TBI. Various types of light flashes and odors were reported in this study.